Effect of Gelling Agent and Selective Sub-culturing on Hyperhydricity in Anther-Derived Coconut Embryos - Perera, P. I. P.; Kularatene, J. D. J. S.; Weerakoon, L. K. (International Coconut Community Journal, 2011)
Experiments were conducted to compare the liquid medium with the media solidified with agar or phytagel. Selective subculturing and use of the embryo maturation medium supplemented with higher concentration of phytagel (0.5%; w/v) were also tested for reducing the vitrified embryos. Modified Eeuwens Y3 medium was used as the basal medium. By culturing the anthers on the medium solidified with phytagel (0.25%; w/v), direct embryo formation (86.7%) and embryo conversion (21.5%) were significantly increased. Plant regeneration efficiency of anther derived embryos or calluses developed in the liquid culture medium was extremely low (2.4%). Vitrification was further reduced by incorporating 0.5% (w/v) phytagel into the embryo maturation medium. Highest plant regeneration efficiency was obtained by exposing the embryos to 0.5% (w/v) phytagel for 21 days, which reduced vitrification by 42%. Furthermore, selective subculturing of the embryos was effective for reducing vitrification.